2017
DOI: 10.1016/j.neulet.2017.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of cerebral microbleeds following traumatic brain injury using MRI in the hyper-acute phase

Abstract: HighlightsTraumatic cerebral microbleeds (TCMBS) can be identified using susceptibility weighted imaging in the first few hours after injury.TCMBs are a useful indicator of severity in this time frame.The presence of TCMBs is an early indicator of injury severity following trauma.There is a relationship between decreasing size of TCMBs and recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 23 publications
(37 reference statements)
1
33
0
Order By: Relevance
“…Similar changes in CMB volume have previously been reported during the acute and chronic phases following a traumatic brain injury. [24][25][26] Liu et al found a dramatic decrease in quantitative measures of CMBs from serial imaging acquired beyond 2 years postinjury, 24 while Lawrence et al and Watanabe et al reported the appearance of CMBs within the first few hours following injury; CMBs showed reductions in volume over a 2-15-day period that were associated with patient recovery. 25,26 Thus, identifying treatment strategies to accelerate the mechanism through which CMBs decrease in size may be a viable alternative for minimizing CMBassociated deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Similar changes in CMB volume have previously been reported during the acute and chronic phases following a traumatic brain injury. [24][25][26] Liu et al found a dramatic decrease in quantitative measures of CMBs from serial imaging acquired beyond 2 years postinjury, 24 while Lawrence et al and Watanabe et al reported the appearance of CMBs within the first few hours following injury; CMBs showed reductions in volume over a 2-15-day period that were associated with patient recovery. 25,26 Thus, identifying treatment strategies to accelerate the mechanism through which CMBs decrease in size may be a viable alternative for minimizing CMBassociated deficits.…”
Section: Discussionmentioning
confidence: 99%
“…This can be debated as "tissue at risk" may well be identified. Nevertheless, MRI is seen as very useful in predicting short-term and long-term functional outcome (16,17). Neurointensivists, nowadays, are confronted with the dilemma when to perform MRI in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…The scanning protocol included T1-weighted MPRAGE, T2-weighted Turbo spin echo and T2* susceptibility weighted structural imaging (SWI) sequences, 2D proton magnetic resonance spectroscopic (MRS) chemical shift imaging (CSI) and diffusion-weighted imaging. SWI findings for a subset of this study population have been reported previously (45). Single-slab multi-voxel MRSI data were acquired using a point-resolved spectroscopy (PRESS) sequence using the following parameters: TR = 1700 ms, TE = 135 ms. Six saturation bands were applied (40 mm superior and inferior, 50 mm anterior, posterior, right and left lateral).…”
Section: Mri Data Acquisitionmentioning
confidence: 99%